Ethical Decision Making in Multinational Organizations: A Culture-Based Model - Robertson, Chris (Journal of business ethics, 1999)
The purpose of this paper is to analyze the relationship between national culture and ethical decision making. Established theories of ethics and moral development are reviewed and a culture-based model of ethical decision making in organizations is derived. Although the body of knowledge in both cross-cultural management and ethics is well documented, researchers have failed to integrate the influence of cultural values into the ethical decision-making paradigm. A conceptual understanding of how managers from different nations make decisions about highly ethical issues will provide business ethics researchers with a sound theoretical foundation upon which future empirical inquiry can be based.